(untitled) (Eurasian Journal of Philology Science and Education, 2023)
In linguistics metaphor has been recognized as a figurative word that serves artistic and journalistic style as a descriptive-decorative tool. But we did not pay much attention to the name-creating function of metaphor, to the fact that it is a tool that brings out the mental actions (associations, stereotypes) of a person through language. Metaphor’s property of revealing the true world, including universal logical knowledge (primitive image of the world), stereotypical knowledge of the nation (national image of the world), as well as the basic knowledge of the people, aesthetic taste, etc. It is also clear that the universal unity that represents the collected informational knowledge (conceptual image of the world) began to be determined when the anthropological paradigm entered linguistics. From this point of view, a close study of the functions of metaphor and determination of its influence on the enrichment and preservation of the linguistic fund was one of the objective prerequisites of our work. Therefore, in the article, before defining the anthropological and cultural functions of metaphor, we aimed to distinguish its functions in the linguistic system. In the framework of structural linguistics, the verbal expression of the law of simile metaphor was limited only to the determination of its meaning in the linguistic system. And how it is formed in a person’s thinking system, the knowledge, state of mind, the level of recognition of the true world, i.e., the processes of thought operations before the metaphor was revealed as a language, were not studied. Therefore, in order to study these processes, it is proved that it is very important to study the role and functions of linguistic metaphor.